Switching power supplies A to Z - Maniktala, Sanjaya, ....- (Amsterdam : Elsevier, 2012)
This book is the most comprehensive study available of the theoretical and practical aspects of controlling and measuring Electromagnetic Interference in switching power supplies, including input filter instability considerations. The new edition is thoroughly revised with six completely new chapters, while the existing EMI chapters are expanded to include many more step-by-step numerical examples and key derivations and EMI mitigation techniques. New topics cover the length and breadth of modern switching power conversion techniques, lucidly explained in simple but thorough terms, now with uniquely detailed "wall-reference charts" providing easy access to even complex topics. Step-by-step and iterative approach for calculating high-frequency losses in forward converter transformers, including Proximity losses based on Dowell's equations Thorough, yet uniquely simple design flow-chart for building DC-DC converters and their magnetic components under typical wide-input supply conditions Step-by-step, solved examples for stabilizing control loops of all three major topologies, using either transconductance or conventional operational amplifiers, and either current-mode or voltage-mode control.
Includes bibliographical references (pages 721-722) and index.
Keywords: Switching power supplies